Navigering i en djungel av hållbara fonder - Stepnik,Dominika; Olsson,Sissy; Palm,Anna (2023)
The purpose of this essay is to map how a selection of Swedish banks' and fund companies' marketing of sustainable funds relates to the complex definition of sustainability, as well as provide insight into the current interpretation problems. The study's qualitative method has an abductive strategy with a hermeneutic approach. The primary data has been collected through six semi-structured interviews with employees from a selection of case companies in the financial industry and then analyzed using a theoretical framework. The theoretical framework presents a number of different theoretical and legal definitions of sustainability. Additionally, theories that contribute insight to the financial market, explain the behavior of market participants as well as their motivation to integrate sustainability in their work are included. The empirical foundation is presented based on the interviewees answers and is structured according to themes that have emerged during the data review. This has then been analyzed using the theoretical framework and the method of sorting, reduction and argumentation. The study has determined that there is an interpretation problem with the concept of sustainability in Swedish banks' and fund companies' marketing. This is mainly seen in their communication of Article 8 and 9 funds. Consumers thus risk being misled and miss out on the offer they want. The information related to the funds degree of sustainability must therefore be clarified.
Keywords: Hållbarhet; Marknadsföring; Hållbara fonder; Tolkningsproblematik; Asymmetrisk information